Dihydromyricetin improves growth performance, immunity, and intestinal functions in weaned pigs challenged by enterotoxigenic Escherichia coli - Xie, Kunhong; Qi, Jiawen; Deng, Lili; Yu, Bing; Luo, Yuheng; Huang, Zhiqing; Mao, Xiangbing; Yu, Jie; Zheng, Ping; Yan, Hui; Li, Yan; Li, Hua; et al. (Frontiers in Veterinary Science, 2024)
Enteric infection is a major cause of enteric disorder in neonatal pigs during the weaning transition. Dihydromyricetin (DMY) is a natural flavanonol compound extracted from Ampelopsis grossedentata with numerous biological activities such as antioxidative and immunomodulatory functions. The objective of this study was to investigate the effects of dietary dihydromyricetin supplementation on growth performance, immunity, and intestinal functions in weaned pigs challenged by enterotoxigenic Escherichia coli (ETEC). In total, 24 weaned DLY (Duroc × Landrace × Yorkshire) pigs were allotted to 3 treatments. Pigs fed with basal diet or basal diet containing 300 mg/kg DMY were orally infused with sterilized culture or ETEC (2.5 × 1011 colony-forming units). Dietary DMY supplementation significantly elevated the final weight and average daily gain (ADG) but reduced diarrhea incidence in the weaned pigs of the EDMY group compared to the pigs of the ECON group (p < 0.05). Compared to the ECON group, DMY also improved the digestibility of dry matter (DM), ether extract (EE), gross energy (GE), and ash of the EDMY group (p < 0.05). Moreover, DMY not only significantly decreased the ratio of albumin/globulin but also elevated serum concentrations of immunoglobulins (e.g., IgA and IgG) in the weaned pigs of the EDMY group compared to the pigs of the ECON group (p < 0.05). Interestingly, the villus height, the ratio of villus height to crypt depth (V:C), and the activities of mucosal alkaline phosphatase, sucrase, and maltase in the duodenum and jejunum of the EDMY group were higher than those in the ECON group (p < 0.05). Importantly, DMY significantly elevated the expression levels of jejunal zonula occludens-1 (ZO-1), claudin-1, cationic amino acid transporter-1 (CAT-1), and fatty acid transport protein-1 (FATP-1) in the weaned pigs of the EDMY group compared to the pigs of the ECON group (p < 0.05). Additionally, compared to the ECON group, DMY increased the concentrations of microbial SCFA metabolites (e.g., acetic acid and propanoic acid), but reduced the abundance of Escherichia coli in the cecum of the EDMY group (p < 0.05). Dietary DMY supplementation can attenuate the ETEC–induced growth retardation and intestinal injury, which was attributed to the amelioration of intestinal nutrient digestion and transport functions as well as the improved microbiota.